Epidemiological Characteristic of Aphthous Stomatitis and Real Clinical Practice of Management of Patients in Uzbekistan - D.M. Alimova1, O.E. Bekjanova2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The article provides an epidemiological description for patients with chronic recurrentaphthous stomatitis (RAS) and the frequency of their reversal in the general structure of diseases of the oralmucosa from 2014 to 2018. The structure of clinical forms of RAS in the Republic of Uzbekistan (ICD-10) was taken. The study of the dynamics of frequency and debut of various clinical forms of RAS, thegender characteristics of RAS has led to the need for the introduction of modern standards for examination,treatment, and prevention of the disease. The goal of the research is to study the frequency of occurrenceof RAS, as well as the real clinical practice of managing patients in the Republic of Uzbekistan and itscompliance with existing recommendations.Materials and Method: Patients’ medical records and records of the patients’ consultation journal for fiveyears of work (from 2014 to 2018) were studied.Results: Taking into account the gender and age characteristics of patients with RAS will determine the realclinical picture and prevalence of this disease, increase the ability of monitoring, medical examination andproviding timely specialized care, allowing to prevent the progression and maintain the working capacity ofpatients with this pathology of OCR.Conclusion: The frequency of RAS at the general reception for diseases of OCR is 6.22 ± 0.42%; in thegeneral structure of the disease, the fibrinous form prevails 3.46%; the incidence of necrotic periadenitis is3.15%; herpetiform aphthous stomatitis is recorded in 2.25% of patients and 1.25% - a symptom in Behcet’sdisease. The debut of RAS falls on the age period of 18-34 years (62.50%), which indicates a negativetrend of “rejuvenation” of this pathology. For effective treatment and rehabilitation of patients sufferingfrom RAS, it is necessary to conduct a comprehensive examination attracting internists, an appointmentof means of immunomodulating therapy and means effectively correcting the most important homeostaticmechanisms in humans.